(untitled) (MASKAY, 2013)
This project describes the design and implementation of Teleoperation, Data Acquisition, Fuzzy Speed Control, and 2D Environment Mapping applications for the Pioneer P3-DX mobile platform through sonar, odometry, and free GNU/Linux software. The project provides a guide to using programming concepts in Python, which allows the creation of applications in a versatile way through the use of libraries such as GTK for the development of the graphical environment, PYFUZZY for the development of the fuzzy speed controller, and OpenCV to show the maps of the environment.